Effectiveness of a nurse-led self-management support program on knowledge, self-management behavior, self-efficacy and quality of life among kidney patients - Al Sawad, Ayat Ali A (2022)
Background: The complexity of chronic kidney disease (CKD) and its treatments have made self-management behavior inevitably challenging. Evidence indicates that providing education with self-management skills may improve numerous health outcomes in patients with pre-dialysis CKD. Aim: This PhD thesis aims to examine the effectiveness of a locally developed nurse-led self-management support program (CKDNLSM) for patients with CKD stages 3-4. Methods: Three phases were planned to achieve the study aims. In Phase 1, three instruments namely the Kidney Disease Knowledge Survey [KiKS], the CKD Self-Management [CKD-SM], and the Self- Efficacy for Managing Chronic Disease [SEMCD] were translated, culturally adapted, and validated to be used in Phase 3. In Phase 2, a co-design approach was used to develop the CKD-NLSM intervention for patients with CKD stages 3-4 based on the Social Cognitive Theory. In Phase 3, the CKD-NLSM was evaluated in a randomized controlled trial (RCT) of its effectiveness compared to standard usual care on kidney disease knowledge, CKD self-management behavior, self-efficacy, quality of life, blood pressure control, and adherence to CKD diet estimated by dietary protein intake, dietary sodium intake, and dietary acid load. The parallel RCT was conducted in adult with CKD stages 3–4, aged 18 years and above in a tertiary teaching hospital. The CKD-NLSM intervention comprises 6-week program in addition to standard usual care, while the control group received standard usual care. All outcomes were measured at baseline and 26 weeks post-baseline (modified due to the social restrictions caused by the COVID-19 pandemic). The between- and within-group intervention effects were estimated using two-way repeated measure ANOVA/ANCOVA for normally distributed variables while Generalized Estimating Equation (GEE) for non-normal distributed variables. The group effects were tested as Time*Group. Results: A total of 130 patients with CKD stages 3- 4 participated in the parallel RCT with 66 randomized to the CKD-NLSM and 64 to control group. Baseline characteristics between the control and intervention patients were comparable except education, age, and CKD-stages. The mean (SD) for age was 61.7 (12.02) years (intervention), and 68.1 (10.13) (control). The majority in the intervention group (57.6%) were at stage 3b while in control group were at stages 3a and 3b in equally proportion totaled at 75%. CKD-NLSM improved participants’ total kidney disease knowledge (24.6±0.36 versus 14.5±0.54, p<0.001), total CKD self- management behavior (81.0±1.24 versus 65.4±1.67, p<0.001) and self-efficacy (44.9±0.84 versus 30.1±1.33, p<0.001). Within-group improvement was also observed, except in quality of life. There were no significant differences in systolic blood pressure control and adherence to diets estimated by dietary protein intake, dietary sodium intake, and dietary acid load. Conclusion: CKD-NLSM is effective in improving kidney-specific knowledge, CKD self-management behavior and self-efficacy in patients with CKD stages 3-4. A larger and longer study is needed to examine the effect of CKD-NLSM on dietary protein intake, dietary sodium intake, and dietary acid load (adherence to diet control), quality of life, kidney functions and progression.